2019
DOI: 10.1159/000496343
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Risk Factors and Findings on Brain MRI of Elderly Adult American Indians: The Strong Heart Study

Abstract: Background: Clinical stroke is prevalent in American Indians, but the risk factors for cerebrovascular pathology have not been well-studied in this population. The purpose of this study was to correlate abnormalities on brain magnetic resonance imaging (MRI) with clinical risk factors in a cohort of elderly American Indians. Methods: Brain MRI scans from 789 participants of the Strong Heart Study were analyzed for infarcts, hemorrhage, white matter disease, and measures of cerebral atrophy including ventricula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…More attention needed to pay to the related research, to evaluate the relationship between polymorphic gene and exposed factors. Hypertension and diabetes usually occurred successively, due to the hardening of blood vessels diabetes could induce hypertension [17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…More attention needed to pay to the related research, to evaluate the relationship between polymorphic gene and exposed factors. Hypertension and diabetes usually occurred successively, due to the hardening of blood vessels diabetes could induce hypertension [17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…WMHs contribute to the pathogenesis of cognitive impairment, and cardiovascular risk factors contribute to the development of WMHs and cognitive impairment. 2 Due to the prominent role of arterial hypertension in WMH development in epidemiological studies, [2][3][4][5][6][7][8][9][10][11][12] blood pressure (BP) represents a target to prevent or slow down progression of WMHs and their clinical consequences. 13 Previous epidemiological studies established the association between BP and WMHs [2][3][4][5][6][7][8][9][10][11][12] but did not elaborate on efficacy of antihypertensive treatment including different stages of BP control even though this represents an important determinant of brain health.…”
mentioning
confidence: 99%
“…This result is consistent with that of previous studies. A previous study of 789 older adults also reported no significant correlation between high HDL levels and brain volume [ 35 ]. Furthermore, Leeuw et al reported that LDL and HDL were not associated with brain volume in 3962 participants [ 36 ].…”
Section: Discussionmentioning
confidence: 94%